2001
DOI: 10.1007/s004280100468
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of E-cadherin and stromelysin-3 expression in de novo and ex adenoma carcinoma of the colorectum

Abstract: An apparent exception to the colorectal adenoma-carcinoma carcinogenetic pathway is the so-called "de novo" carcinoma which has no evidence of adenoma in its vicinity. Despite the fact that they are often quite small, these lesions appear to be more aggressive (i.e., greater likelihood of lymph-node metastases) than carcinomas that clearly arise from surrounding adenomas exadenoma carcinoma. The purpose of the present comparative immunohistochemical study was to compare rates of cell adhesion molecule (E-cadhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…Abnormalities of E-cadherin expression have been described in colorectal carcinoma [28] and have been correlated with increased invasiveness, metastatic potential and poor patient prognosis in this tumor type [29] . Recent research showed that E-cadherin expression was significantly lower in the de novo group tissue than that in the prudent group [30,31] . In the present study, by Western blotting analysis, we also confirmed that LST-R1 cells have a prominent lower expression of E-cadherin than that in several other cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…Abnormalities of E-cadherin expression have been described in colorectal carcinoma [28] and have been correlated with increased invasiveness, metastatic potential and poor patient prognosis in this tumor type [29] . Recent research showed that E-cadherin expression was significantly lower in the de novo group tissue than that in the prudent group [30,31] . In the present study, by Western blotting analysis, we also confirmed that LST-R1 cells have a prominent lower expression of E-cadherin than that in several other cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent publication comparing de novo and ex adenoma carcinomas, we found that E-cadherin was significantly more often less strongly expressed than in a comparable group of ex adenoma carcinomas [50]. Of 42 ex adenoma pT1 carcinomas, 79% retained a normal level of E-cadherin expression compared with just over half of the de novo group (Fig.…”
Section: Cell Adhesion: E-cadherin and Cd44 Expressionmentioning
confidence: 87%
“…We have found that a significantly higher proportion of de novo cases had extensive staining for ST-3 (P=0.014) than in a comparable group of ex adenoma cases (Fig. 13) [50]. ST-3 expression was also significantly associated with more poorly differentiated lesions and showed strong statistical correlation with tumor cell dissociation on the tumor front and, particularly, with the likelihood of vascular invasion.…”
Section: Stromelysin-3 (St-3) Expressionmentioning
confidence: 91%
“…Generally, carcinoma cells are characterized by poor intercellular adhesion, loss of differentiated epithelial morphology and increased cellular motility [16][17][18]. They also feature downregulation or complete shutdown of Ecadherin expression caused by mutation of the E-cadherin gene (CDH1) or other mechanisms that interfere with the integrity of the adherens junctions [3].…”
Section: Discussionmentioning
confidence: 99%